High velocity pulse biopsy device enables controllable and precise needle insertion and high yield tissue acquisition. (February 2018) - Schässburger, Kai-Uwe; Paepke, Stefan; Saracco, Ariel; Azavedo, Edward; Ekström, Christina; Wiksell, Hans
Highlights: New biopsy system for breast and axillary lymph nodes. Pneumatic mechanism intended for better control and precise lesion targeting. Achieves higher needle acceleration, velocity and power compared to current devices. Collects significantly more tissue than standard biopsy device in bench models. Abstract: Minimally invasive biopsies are a cornerstone of breast cancer management with ultrasound being the preferred guidance modality. New developments in breast cancer management and advances in imaging technologies bring new challenges to current biopsy methodologies. A new biopsy device (NeoNavia® biopsy system, 14 G) was developed. It incorporates a pneumatic needle insertion mechanism that is intended to provide better control of needle progression and enable stepwise insertion without noticeable deformation or displacement of surrounding tissue as visualized under ultrasound. A new method of tissue acquisition was designed to achieve a sampling yield higher than standard methodologies. Needle dynamics was assessed on a specifically designed test bed and sampling performance was compared to a Magnum® biopsy instrument (Bard, Covington, GA, USA) in representative tissue models. The histological quality of samples obtained ex-vivo was evaluated. A pneumatic pulse was measured to accelerate the needle to a maximum velocity of 21.2 ± 2.5 m/s on a stroke length of 2.5 mm, achieving significantly higher acceleration, maximum velocity and power than current biopsy devices. Mean weight of samples obtained by the NeoNavia device were 3.5, 4.6, and 4.3 times higher when sampling was performed in turkey breast, calf thymus and swine pancreas, respectively, as compared to samples obtained with the Magnum instrument. Ex-vivo analysis indicates that the method of tissue acquisition has no apparent negative impact on the histopathologic quality of obtained samples.